CAPACITY OF MONONUCLEAR CELLS OF PERIPHERAL BLOOD AND BONE MARROW OF PATIENTS WITH APLASTIC ANEMIA TO PRODUCE MULTI-COLONY-STIMULATING FACTOR - IL-3 - O. E. Rozanova (Медицинская иммунология, 2014)
Abstract. The capacity of mononuclear cells of peripheral blood and bone marrow of 36 patients with aplastic anemia to produce multi-colony-stimulating factor - IL-3 have been studied. It was established that the cells of immune system produce the amount of cytokine comparable to normal values, and the depression of hemopoesis in this disease is not connected with insufficient synthesis of IL-3 by mononuclear cells and is possibly due to other factors.